PENGELOLAAN EKOWISATA DAN PENTINGNYA PENERAPAN CHSE - Liliana Dewi; Gagih Pradini; Muhammad Andriansyah Satritama; Reza Ardian Putra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Godong Ijo is an educational tourist attraction that carries the concept of "forest in the middle of the city" has facilities such as restaurants, fishing ponds, educational gardens, children's playgrounds, and mini zoos. This makes Godong Ijo often used as a tourist visit destination both from school children to the general public. Lush rare trees and animals such as squirrels, lizards, toads can still be found at the location and become learning materials for school children. Carrying the theme of ecotourism, Godong Ijo is present as an Education Garden consisting of food plant zones, medicinal plants, herb plants, industrial plants, fruit plants zones and unique and rare plant zones as tourist attractions. Based on observations and interviews, it is known that managers need an understanding of ecotourism management and CHSE guidelines issued by the Ministry of Tourism and Creative Economy, especially for tourist attractions. In an effort to support these needs, the team strives to provide assistance in the form of counseling on understanding ecotourism and its management as well as CHSE (clean, health, safety, environment sustainable) protocols to staff at Godong Ijo with the aim of human resources working in Godong Ijo gaining understanding and understanding of ecotourism management and CHSE Health protocols.